The sustainable port classification framework for enhancing the port coordination system - Othman, Mohammad Khairuddin; Abdul Rahman, Noorul Shaiful Fitri; Ismail, Alisha; Saharuddin, A.H. (Elsevier B.V., 2019)
The port classification framework is not only beneficial for highlighting the background of the ports, but can also be utilized in the benchmarking and comparison of port coordination systems. In Malaysia, the lack of concrete justifications in the existing port classification process had resulted in a debatable framework of port classification development and consequently, confusion among the port stakeholders. As such, this study is conducted with the aim of revising the Malaysian ports’ classification framework according to the global perspective of a sustainable port classification framework through the enhancement of its national port coordination system. By using a qualitative approach of descriptive analysis, the background of the port classification systems was not only analysed according to the Malaysian and global perspectives, the segregation of three different ports classes was also emphasized in the enhancement of the country's port coordination system. Apart from being a comprehensive reference that aids the academicians and stakeholders in the improvement of the existing loopholes in the Malaysian port coordination system, this paper had also offered a sustainable classification framework guideline for decision and policy-makers in the expansion of port competitiveness through a reclassification of the national port operations.